"Die eigene Nuance - Virant, Špela (Vestnik za tuje jezike, 2017)
The article, using discourse analysis and reception theory, concentrates on the concept of individuality in Carl Sternheims comedies known by the title of the play cycle From the Heroic Life of the Bourgeois, with special regard to their reception in the works of the German writers W. G. Sebald and Florian Illies. The focus is on two major concepts that in Sternheim's works are set in the context of his critique of the bourgeois ideology. Those concepts are social criticism and individuality. The analysis of the literary reception shows the numerous changes in the understanding of these concepts that came about due to the changing ideologies during the hundred years since the plays had been written. The rereading of Sternheim's plays shows that the inherent contradictions still remain unresolved.
Keywords: German drama; Sternheim, Carl, 1878-1942; "Aus dem bürgerlichen Heldenleben"; comedy; Literarne študije; literary reception; Sebald, W. G., 1944-2001; nemška dramatika; komedija; recepcija